Curbing the Killing Fields: Making South Africa Safer. Issue 1 (March 2014) - van der Spuy, Elrena; Shearing, Clifford
South Africa is often held up as an enviable example of a country that avoided a full-blown civil war. Twenty years into the new constitutional democracy, however, the continuation of social conflict and criminal violence begs the question as to whether South Africa deserves to be described as "postconflict." In this article, we take stock of contemporary conversations about crime. First, key dimensions of South Africa's crime problem are described, drawing on a composite report on violent crime published in 2009 by the Centre for the Study of Violence and Reconciliation (Johannesburg). We then focus on three recent episodes to illustrate some of the dimensions of violence in South Africa's multifaceted society. Finally, we take stock of some select approaches to dealing with violent criminality and review ideas for containing crime and making South Africa safer.